Increased short‐ and long‐term mortality following infections in dementia: a nationwide registry‐based cohort study. (9th November 2020) - Janbek, J.; Taudorf, L.; Musaeus, C. S.; Frimodt‐Møller, N.; Laursen, T. M.; Waldemar, G.
Abstract : Background and purpose: Mortality following infections in dementia has not yet been comprehensively explored. The aim of this cohort study was to investigate the short‐ and long‐term mortality following infections in dementia. Methods: Follow‐up was from 1 January 2000 or the 65‐year birthday until death, immigration, or 31 December 2015. Exposure was incident dementia and a first infection. The outcome was all‐cause mortality. Mortality rate ratios (MRRs) were calculated using Poisson regression in 4 exposure groups (dementia yes/no, infection yes/no) by sex, infection site, and time since infection. Results: 1, 496, 436 people were followed with 12, 739, 135 person‐years. MRR in dementia/infection was 6.52 (95% confidence interval: 6.43–6.60) and was increased for infections of all sites. Increased mortality was short term (30 days) and long term (10 years). Conclusions: Increased mortality in people with dementia identifies them as a particularly vulnerable group that needs clinical attention. Abstract : More than 1.4 million people 65 years of age or older were followed in Danish registry data. Findings show that people with dementia have a substantially increased mortality rate (sixfold) following an infection that goes beyond the mortality rates observed in people with dementia alone, infections alone, or the sum of these rates. Increased mortality was observed following all types of infections (highest for sepsis and lowest for ear infections) and was both short term (30 days) and long term (10 years).